Inulin and Creatinine Clearances in Children with Renal Disease - Lydia Kosnadi (Indonesian Pediatric Society, 1997)
To know how far the kidneys have been damaged, renal function in children suffering from renal disease must be measured. The aim of this study was to measure inulirs and creatinine clearances in children suffering from renal diseases, and to know how would be the correlation between them. In this cross-sectional study sample size was estimated by the one-sample for estimating the population proporÂtion, and data analysis was done by die Pearson product moment correlation and analysis of variance. Simultaneous measurements of inulin and creatinine clearance levels in 112 children were performed at Kariadi General Hospital, Telogorejo Hospital and St Elisabeth Hospital in Semarang, over the period from March 1991 to July 1993. Creatinine clearance (CJ showed positive correlation with inulin clearance (CJ in all patients with mixed (normal and decreased) renal functions: Ctr= 8,41 + 1,00 C n (r = 0,99; p <0,001; n = 112). Further it revealed that the difference between these two clearances was a function of the severity of the renal failure. These results were in accordance with those published in previous studies.